Defect-induced electronic structures on SnSe surfaces. (18th June 2019) - Asakawa, Kanta; Oguro, Fumikazu; Yoshida, Yasuo; Sakai, Hideaki; Hanasaki, Noriaki; Hasegawa, Yukio
Abstract: Using a low-temperature scanning tunneling microscope (STM), we investigated the role of atomic-scale defects of a cleaved SnSe(100) surface on the electronic structure around them. We found in empty-state STM images that Sn vacancies induce dark contrast around them, proving their role as a p-type dopant. The vacancies are also accompanied with an X-shaped dark pattern reflecting the structural asymmetry of the terminating layer. In addition, in empty-state STM images, a 1 × 3 superstructure was observed around a bright-contrasted defect, which is presumed to be a defect-induced charge density wave driven by strong electron-phonon interaction.